2013
DOI: 10.1523/jneurosci.4610-12.2013
|View full text |Cite|
|
Sign up to set email alerts
|

Elevation of Brain Magnesium Prevents and Reverses Cognitive Deficits and Synaptic Loss in Alzheimer's Disease Mouse Model

Abstract: Profound synapse loss is one of the major pathological hallmarks associated with Alzheimer's disease (AD) and might underlie memory impairment. Our previous work demonstrated that the magnesium ion is a critical factor in controlling synapse density/plasticity. Here, we investigated whether elevation of brain magnesium by the use of a recently developed compound, magnesium-L-threonate (MgT), can ameliorate the AD-like pathologies and cognitive deficits in the APPswe/PS1dE9 mice, a transgenic (Tg) mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 8 publications
9
59
0
Order By: Relevance
“…MgT treatment improved the cognitive decline of the APP/PS1 mice after 5 mo of administration. In agreement with our observations, Li et al (2) found that MgT attenuates cognitive decline in APP/PS1 mice. Similar observations have been reported in rats and humans (39,40).…”
supporting
confidence: 94%
“…MgT treatment improved the cognitive decline of the APP/PS1 mice after 5 mo of administration. In agreement with our observations, Li et al (2) found that MgT attenuates cognitive decline in APP/PS1 mice. Similar observations have been reported in rats and humans (39,40).…”
supporting
confidence: 94%
“…Our data are consistent with a growing animal literature suggesting that chronic MgT treatment may have clinical relevance since it has been shown to reduce learned helplessness (a model of human depression; Abumaria et al, 2009), enhance the efficacy of fear extinction (Abumaria et al, 2011), and reduce cognitive deficits in a mouse model of Alzheimer’s Disease (Liu et al, 2009). Here we demonstrated that MgT increased the rate of CTA extinction, reduced SR of a CTA, and interacted with EU extinction procedures to further reduce SR of a CTA.…”
Section: Discussionsupporting
confidence: 90%
“…Selective exploration of the novel object is taken as evidence that the preexposed object is recognised as familiar. This widely-used task has revealed deficits in a wide range of different 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 transgenic models of AD [32], and impairments are routinely observed in older APPswe/PS1dE9 mice [33,34,35,36,37; but see 38]. SOR deficits are also occasionally reported in these mice at 6-7 months of age [34,39,40,41], but never in animals younger than 6 months [40,42].…”
Section: Introductionmentioning
confidence: 99%